Impact of the Dissipation on the Nonlinear Interactions and Turbulence of Gravity-Capillary Waves - Michael Berhanu (Fluids, 2022)
Gravity-capillary waves at the water surface are an obvious example illustrating wave propagation in the laboratory, and also nonlinear wave phenomena such as wave interactions or wave turbulence. However, at high-enough frequencies or small scales (i.e., the frequencies typically above 4 Hz or wavelengths below 10 cm), the viscous dissipation cannot be neglected, which complicates experimental, theoretical, and numerical approaches. In this review, we first derive, from the fundamental principles, the features of the gravity-capillary waves. We then discuss the origin and the magnitude of the viscous wave. dissipation in the laboratory and under field conditions. We then show that the significant level of dissipation has important consequences on nonlinear effects involving waves. The nonlinearity level quantified by the wave steepness must be large enough to overcome the viscous dissipation. Specifically, using water as fluid in the field and in the laboratory, nonlinear wave interactions and wave turbulence occur most of the time in a non-weakly nonlinear regime, when the waves are in the capillary or gravity-capillary range.